Capillary Filling of Nanoscale Channels and Surface Structure. Issue 11 (11th September 2014) - Kriel, Frederik H.; Sedev, Rossen; Priest, Craig
Abstract Nanoscale surface structures and channels are of intense interest for the very high surface‐to‐volume ratios involved. For extremely small systems, it may become difficult to distinguish between bulk and interface as well as their respective effects on the fluid volume. We review capillary filling of nanochannels and wicking in nanoscale surface structures. Both processes are of fundamental importance for the initial filling and successful operation of nanofluidic devices. We conclude that, despite the small scales involved, Washburn's description of the spontaneous capillary filling of nanochannels is reliable. Similarly, nanowicking follows conventional capillarity theory closely. Nonetheless, open questions remain about the role and significance of line tension, precursor films and contact line pinning. The exact consequences of a diffuse interface or contact line are yet to be fully understood.